Ação antimicrobiana de diferentes soluções irrigadoras sobre biofilme misto de Enterococcus faecalis e Candida albicans utilizando um modelo experimental com dentes bovinos - Monteiro, Samila dos Santos Gonçalves (2015)
Bacteria and their products are the primary etiological agents of pulpal and periapical disease. Most of these bacteria is organized in the form of biofilm. During endodontic treatment, most of these microorganisms is eliminated by chemical-mechanical preparation of the root canal, which is performed using endodontic instruments and irrigation. Sodium hypochlorite (NaOCl) is the irrigant commonly used throughout the world. The Endo-PTC is a substance aid in irrigation facilitating the penetration of substances in the dentinal tubules. Chlorhexidine has been recommended as endodontic because of the broad antimicrobial spectrum. Bacteria causing the pulp and periradicular diseases Enterococcus faecalis is the species most associated with the failure of endodontic treatment. Among the fungi most frequently found in root canals occupies pride of place the yeast species Candida albicans, can also colonize the dentinal tubules and co-exist with other microorganisms. The objective of this study was to evaluate the antimicrobial activity on mixed biofilm Enterococcus faecalis and Candida albicans of different irrigating solutions using a model in vitro and ex vivo. Biofilms were formed in 96-well plates for 21 days. Then, they were placed in contact for 15 minutes with solutions tested and quantitation performed by crystal violet biomass retention and test viability by resazurin. For the former living 120 tests root canals were filled in with E. faecalis and C. albicans to form biofilm and incubated at 21 days of age. Mature biofilms channels were subjected to irrigation with saline, sodium hypochlorite 1%; 2.5% and 5% chlorhexidine and Endo-PTC 2% for 15 minutes. After the treatments, the percentage of bacteria killed by the disinfectants was analyzed by CLSM and counting colony forming units. Saline and 2% chlorhexidine were less effective in the reduction of microorganisms compared to sodium hypochlorite (P <0.05). However, there was no significant difference between sodium hypochlorite 1% and Endo-PTC (P> 0.05). Salt, 2% chlorhexidine and Endo-PTC were the solutions that had a higher proportion of green cells after application.